Photoelectrochemical water splitting under concentrated sunlight: best practices and protocols - Li, Kejian; Dong, Wan Jae; Mi, Zetian (Frontiers in Energy Research, 2025)
Photoelectrochemical (PEC) water splitting is a promising technology for green hydrogen production by harnessing solar energy. Traditionally, this sustainable approach is studied under light intensity of 100 mW/cm2 mimicking the natural solar irradiation at the Earth’s surface. Sunlight can be easily concentrated using simple optical systems like Fresnel lens to enhance charge carrier generation and hydrogen production in PEC water splitting. Despite the great potentials, this strategy has not been extensively studied and faces challenges related to the stability of photoelectrodes. To prompt the investigations and applications, this work outlines the best practices and protocols for conducting PEC solar water splitting under concentrated sunlight illumination, incorporating our recent advancements and providing some experimental guidelines. The key factors such as light source calibration, photoelectrode preparation, PEC cell configuration, and long-term stability test are discussed to ensure reproducible and high performance. Additionally, the challenges of the expected photothermal effect and the heat energy utilization strategy are discussed.